Differential enrichment of bacteria and phages in the vaginal microbiomes in PCOS and obesity: shotgun sequencing analysis - Zheng, Senlin; Chen, Huimin; Yang, Hongyi; Zheng, Xulan; Fu, Tengwei; Qiu, Xiaoyan; Wang, Meiqin (Frontiers in Microbiomes, 2024)
Introduction Previous research has linked vaginal bacteria to polycystic ovary syndrome (PCOS) and obesity in women, yet the specific disparities in vaginal microbiota between these conditions remain unclear. Methods In this study, we aimed to elucidate the contribution of dysregulated vaginal microbiota to PCOS and obesity by analyzing the vaginal microbiota in reproductive-aged women with and without PCOS, as well as obese and non-obese women, using shotgun sequencing. Results Swab specimens were collected from four groups of subjects: PCOS and obese, PCOS and non-obese, non-PCOS and obese, and non-PCOS and non-obese. A total of 333 bacteria and 24 viruses/phages were identified to the species level. Clustering analysis revealed that non-PCOS and non-obese individuals exhibit a similar “healthy” vaginal microbiome, while both obesity and PCOS were associated with microbial dysbiosis. Significant differences in abundance were observed for 26 bacterial species and 6 phages/viruses between groups. Notably, pathobionts such as Streptococcus pyogenes, Leptospira santarosai, Citrobacter amalonaticus, Listeria ivanovii, and Clostridium perfringens were significantly less abundant or absent in the non-PCOS and non-obese group. Furthermore, the abundance of Lactobacillus, Pseudomonas bacteria, and their corresponding phages exhibited positive correlations. Lactobacillus bacteria, lactobacillus phage, and pseudomonas phage/virus were identified as indicators of a healthy vaginal microbiome. Importantly, the differentially enriched bacteria in the PCOS and obesity groups were distinct. Discussion This study confirms that PCOS and obesity are associated with differing enrichment of bacteria and viruses/phages, with both conditions linked to microbial dysbiosis. Moreover, our findings suggest that vaginal phage diversity is associated with a healthy vaginal microbiota, while dysbiosis is associated with a decrease in phages alongside increased bacterial diversity.